Electronic Technology and Civil Procedure
XVI, 332 p.
Keywords: This book contains the seven main reports and eleven correferates of the 2010 International Association of Procedural Law Conference in Pecs. During this conference, participants from around the world examined all aspects of the impact of modern information technology on civil procedure, ranging from the electronic submission of the application to electronic service of documents and electronic means of proof supported by modern information technology. In addition to practical issues, they discussed the possible impact of electronic procedures on traditional principles of civil procedure. The IAPL was the first to put the effect of modern and communication technology on civil procedure on the agenda, in 1999. This confirmed Lord Woolf’s statement from the 90’s, that “IT will not only assist in streamlining and improving our existing systems and process; it is also likely, in due course, itself to be catalyst for radical change as well...”.